Business Development Strategy of PT. Surya Family Capital as An Investment Advisory Company and Investment Manager - Surya Sambudi, Eka; Hakim, Abdurrahman (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to develop a comprehensive business strategy for PT Surya Family Capital as it transforms into an investment advisory and asset management service provider, enabling the company to capitalize on the growing capital market while addressing the challenges posed by low financial literacy in Indonesia. Design/Methodology/Approach – This study employs a qualitative descriptive research approach to analyze the company’s business conditions and identify strategic development opportunities. The business planning process covers key functional aspects, including product and service design, marketing strategy, operations, organization and management, and financial planning. The analysis is intended to evaluate business feasibility and formulate strategies that support sustainable growth. Findings – The results indicate that the proposed business plan for PT Surya Family Capital is feasible for implementation. The recommended strategy emphasizes service innovation, personalized client advisory services, and operational efficiency to enhance service quality and strengthen customer trust. These strategic initiatives are expected to improve the company's competitiveness and enable it to respond effectively to the evolving dynamics of Indonesia’s capital market. Originality/Value This research provides value by designing an integrated business strategy for a newly transformed investment advisory and asset management firm, offering a practical model that strengthens client trust through service innovation and personalized solutions.